Crystallisation behaviour of polyamide-12 during additive manufacturing process - Teo, Benjamin How Wei (2023)
Polyamide 12 (PA12) is a semi-crystalline polymer as its crystallisation behaviour varies due to manufacturing conditions. In this work, the crystallisation behaviour of PA12 was observed through experiments conducted at a constant cooling rate from different maximum heated temperatures. From the differential scanning calorimetry (DSC) experiment, PA12 exposed at a higher temperature crystallised at a lower temperature. The crystallisation shrinkage observed from thermomechanical analysis (TMA) was lower after PA12 was exposed at a higher temperature. Judging from the crystal growth process of PA12 from in-situ optical microscope and phase field modelling, the crystals of PA12 exposed at a higher temperature were found to be smaller and more compact. The exposure to a high temperature allows PA12 to have lower melt viscosity, ensuring the material to sinter evenly, and this enhances better molecular interactions from polymer chains for the formation of crystals.